Lime rates and incorporation method during the reapplication on Tifton perennial pasture (Cynodon spp.) (Revista de Ciências Agroveterinárias, 2010)
The use of high doses of N fertilizers in perennial pastures may require the correction of soil acidity periodically. For some species of tropical perennial pastures, such as tifton, there are no studies in southern Brazil about the best rate and method of incorporating lime during its reapplication in perennial pastures. The objective of this study was to evaluate the efficiency of lime rates applied on the soil surface or incorporated with light harrowing on the Tifton 85 forage yield. The experiment was set in a Red Oxisol in Chapecó, Santa Catarina State, South of Brazil, in 2007. The Tifton pasture was four years-old and soil pH was 4.9. The experimental design was a randomized block with split plots in bands and four replications. Lime rates were tested in the main plots. The method of lime incorporation was assessed in the split plots. Lime rates were 0.0, 4.25 and 8.5 t ha-1, corresponding to rates of 0, 0.5 and 1 times the estimated dose by the SMP method to raise the pH-H2O to 5.5. Each rate was applied with and without incorporation with light harrowing. The pasture dry matter production was measured over a year. There was no pasture response to lime rates, showing that Tifton had low response to soil liming. Lime incorporation with harrow decreased dry matter production in the first cut after harrowing, but the effect was small, not affecting total dry mass production in one year.
Keywords: Acidity correction; Degraded pastures; Liming; Reacidification.